2015
DOI: 10.1158/2326-6066.cir-14-0120
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Innate Immunity and CD90+ NK1.1− Lymphocytes to Treat Established Melanoma with Chemo-Immunotherapy

Abstract: We sought to define cellular immune mechanisms of synergy between tumor-antigen–targeted monoclonal antibodies and chemotherapy. Established B16 melanoma in mice was treated with cytotoxic doses of cyclophosphamide in combination with an antibody targeting tyrosinase-related protein 1 (αTRP1), a native melanoma differentiation antigen. We find that Fcγ receptors are required for efficacy, showing that antitumor activity of combination therapy is immune mediated. Rag1−/− mice deficient in adaptive immunity are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Some studies set the endpoint as the time when the melanoma reached a certain size. 13,14) Others set the endpoint as a certain day (from day 6 to 28) after melanoma cells were implanted, though the basis for selecting the day was not provided. [15][16][17][18] In the beginning of our study, we considered measuring the tumor volume over time, but opted not to do so because of the inaccuracy due to the irregular shape of the tumor formed by the melanoma cells used in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies set the endpoint as the time when the melanoma reached a certain size. 13,14) Others set the endpoint as a certain day (from day 6 to 28) after melanoma cells were implanted, though the basis for selecting the day was not provided. [15][16][17][18] In the beginning of our study, we considered measuring the tumor volume over time, but opted not to do so because of the inaccuracy due to the irregular shape of the tumor formed by the melanoma cells used in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lotfi et al (68) and Ikutani et al (69) reported that ILC2s had increased expression levels of IL-5 in tumor tissue that resulted in the recruitment and activation of eosinophils, which was linked to an improved prognosis in numerous types of solid tumor. More recently, a subset of NK1.1-negative ILCs was reported to be responsible for the impact of a combined chemotherapy and immunotherapy treatment regimen in a murine B16 melanoma model, highlighting the potential anti-tumor role for ILC2s and/or ILC3s (70). Conversely, in certain cases, LTi-cell recruitment in melanoma was reported to be correlated with the expression of CCL21 in the tumor, which was discovered to be a signal to transform the tumor microenvironment from immunogenic to tolerogenic, which subsequently promoted immune evasion (71).…”
Section: Mouse and Ilc3smentioning
confidence: 99%
“…The protective role of ILC3s has been directly revealed for its contribution to the formation of protective tumor-associated tertiary lymphoid structures in non-small cell lung cancer (NSCLC)[ 134 ]. The ILC3s are able to up-regulate adhesion molecules in the tumor microenvironment to enhance leukocyte invasion, and have been characterized as important mediators of the efficacy of a combination therapy of chemotherapy and tumor antigen-targeted monoclonal antibodies[ 135 ]. Though there is no direct evidence linking ILC3s and liver cancer, the connection can be inferred according to their role in colorectal cancer, as well as the ambiguous roles of their downstream effector cytokines, including IL-22 and IL-17.…”
Section: Liver Cancermentioning
confidence: 99%